Maternal and Fetal Outcomes of Pregnancy in Nephrotic Syndrome Due to Primary Glomerulonephritis - Siligato, Rossella; Gembillo, Guido; Cernaro, Valeria; Torre, Francesco; Salvo, Antonino; Granese, Roberta; Santoro, Domenico (Frontiers in Medicine, 2020)
Chronic kidney disease (CKD) affects 3% of pregnancies, impacting on maternal and fetal outcomes, and at the same time, a recurrent question in nephrology regards gestation impact on kidney function. Observational studies stated that CKD stage, pre-existent hypertension, and proteinuria are the main predictors of possible complications, such as maternal CKD progression, maternal or fetal death, prematurity, small for gestational age (SGA) newborn, or admission to the neonatal intensive care unit. In this regard, given the prominence of proteinuria among other risk factors, we focused on primary nephrotic syndrome in pregnancy, which accounts for 0.028% of cases, and its impact on materno-fetal outcomes and kidney survival. Data extracted from literature are scattered because of the small cohorts investigated in each trial. However, they showed different outcomes for each glomerular disease, with membranous nephropathy (MN) having a better maternal and fetal prognosis than focal and segmental glomerulosclerosis (FSGS), membranoproliferative glomerulonephritis (MPGN), or minimal change disease (MCD). Nephrotic syndrome does not have to discourage women to undertake a pregnancy, but the correct management may include a specific evaluation of risk factors and follow-up for adverse materno-fetal events and/or maternal kidney disease progression.